PENGEMBANGAN BRIMOLANG (APLIKASI BELAJAR GEOMETRI MOLEKUL BUDAYA PALEMBANG) UNTUK PEMBELAJARAN KIMIA DENGAN PENDEKATAN ETNOPEDAGOGI - Wijayanti, Sukma Wahyu (ALOTROP, 2023)
One of the materials in chemistry learning where there are many abstract concepts is the shape of a molecule (Molecular Geometry). An ethnopedagogical approach will make the learning process meaningful because the material is associated with a cultural product from the Palembang area. The research procedure used is Research and Development research developed by Borg & Gall. The preliminary study and development phases were carried out in the first year of this research, while the field trial phase will be carried out in the following year. This research focuses on the development stage which consists of (1) the Initial Product Development Stage in the form of making mobile learning displays, creating application content, and developing applications; (2) the Initial Trial Stage (Learning Media Validation Test) based on media, language, and material experts; and (3) Initial Product Completion Stage. Data collection techniques in this study used a questionnaire. The results of this study indicate that mobile learning based on augmented reality is an added value because it is very flexible and helps students project their understanding. In addition, this application can improve students' spatial abilities and be able to analyze cultural contexts in everyday life in chemistry learning materials